Influence of Product Quality and Digital Business on Micro and Small and Medium Enterprises Income during the COVID-19 Post Pandemic - Heri Satrianto; Baghas Budi Wicaksono; Eso Hernawan (LPPM Universitas Buddhi Dharma, 2023)
This study aims to determine the Effect of Product Quality and Digital businesses on the Income of Micro, Small, and Medium Enterprises during the COVID-19 Post Pandemic. Micro, small and medium enterprises (MSMEs) have an important role in the Indonesian economy. The government of Republic Indonesia also views the importance of the existence of MSME entrepreneurs. The existence of MSMEs can have an impact on increasing people's income and also with service innovations that can attract consumers. The method used is quantitative which is taken, it can be ascertained that t-statistics 8.453> t table 1.985 and the value of sig o.oo <0.05, indicates that the effect of product quality has a positive and significant effect on increasing the income of MSME actors. T-statistics is 6.568 > t table 1.985 and sig o.oo <0.05, this indicates that product quality has a significant and positive effect on increasing the income of MSME actors. While F-statistics 153,927 > from F table 4.09 and sig value 0.000 <0.05 this shows that digital business and product quality criteria have a significant and positive effect on increasing the income of MSME actors during the COVID-19 post pandemic.